First fish record in the lago Belgrano of Argentina and the origin of fish populations in Patagonian lakes - Cione, Alberto Luis (2000)
Fil: Cione, Alberto Luis. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina